PETROLOGY OF BOGDAN KHMELNITSKIY VOLCANO (ITURUP ISLAND, THE KURILS): A MODEL OF FRACTIONATION AND MIXING IN THE MAGMA CHAMBER - Larin N.V.; Bindeman I.N.; Simakin A.G. (My University, 1997)
Geological and petrological features of Quaternary volcanic rocks from Bogdan Khmelnitskiy Volcano were used, along with the results of a mass balance calculation, detailed mineralogy, and crystal size distribution, to elucidate the character of fractionation and mixing that controlled the melt evolution in the magma chamber.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная